(3GdeGFI GdeSjMjI aj GdUfGYI GdWHjIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s ((3gHI Gddg Hf edcG GdeJWHH GdfUQGfj GdJcQjJj s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh Sgd gPG gh GdcJGH GdChd ef cJHfG aj UfGYI GdWH , hbUOfG fJcde ajeG jLH JbOjeg bHd GdTQhY aj Yde GdWH s
(3BNQgG (B:s
(3ChUHg ai Mdbg bgQkG hPdc EPCNP jaRY ef GdeGA hjMb YfOPdc HGddHf heGA GdTYjQ hOgf GdHfaSL hgGgfG afbWY GdcdGe ai gPG GdHGH s
(3Yf fSNI GdeDdas
(3hbGHdgG hUMgG YdjgG LgO GdWGbIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs